Collaborative Learning Approach Towards Students’ Reading Comprehension; Does It Have Any Effect? - Baiq Ayu Puteri Jihan Khairunissa; Dedi Sumarsono; Baiq Sumarni (JUPE : Jurnal Pendidikan Mandala, 2019)
This research was aimed to find out the effect of Collaborative Learning Approach towards students’ reading comprehension at MA Darunnajah Al-Falah Telagawaru in academic year 2018/2019. This research was pre experimental research with one group pre-test and post-test design. The sample was taken from all population of the second grade students of MA Darunnajah Al-Falah Telagawaru which consisted of 23 students. The students were treated by using Collaborative Learning Approach. The instrument of collecting the data used reading test that consisted of 25 items in form multiple choice. The result of technique of data analysis showed that the value of sig two tailed was 0.000. It meant that, the value of t-test was lower than the significance level (0.000 < 0.05), indicated that the alternative hypothesis (Ha) was accepted and the null hypothesis was rejected. Thus, it can be concluded that Collaborative Learning Approach is an appropriate and effective approach for teaching reading because, it has a significant effect towards students’ reading comprehension at MA Darunnajah Al-Falah Telagawaru in Academic Year 2018/2019.